2010
DOI: 10.2353/ajpath.2010.091288
|View full text |Cite
|
Sign up to set email alerts
|

Simian Immunodeficiency Virus Infection Alters Chemokine Networks in Lung Tissues of Cynomolgus Macaques

Abstract: Infection by HIV-1 frequently leads to pulmonary complications, including alterations to local immune environments. To better understand these alterations, we have examined in detail the patterns and levels of expression of chemokine, cytokine, and chemokine receptor mRNAs in lung tissues from 16 uninfected or simian immunodeficiency virus ( Pulmonary diseases are frequent complications of HIV-1 infection, affecting 75% to 85% of patients with AIDS.1 In addition, Pneumocystis carinii (now called Pneumocystis j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 54 publications
(53 reference statements)
1
19
0
Order By: Relevance
“…These studies are further complicated by alterations in the lung environment associated with changes in immune status (immunocompetent versus immunosuppressed) and the presence of coinfection (e.g., HIV). Comprehensive evaluations of the effects of Pneumocystis on gene expression of AMs and lung tissue are beginning to address the complexity of the host-pathogen interaction (37,248). In this regard, in order to assess the influence of Pneumocystis in the lung in the association with SIV infection, Qin et al evaluated cytokine and chemokine gene expression changes in lung tissue in SIV-infected macaques with and without PCP (248).…”
Section: Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are further complicated by alterations in the lung environment associated with changes in immune status (immunocompetent versus immunosuppressed) and the presence of coinfection (e.g., HIV). Comprehensive evaluations of the effects of Pneumocystis on gene expression of AMs and lung tissue are beginning to address the complexity of the host-pathogen interaction (37,248). In this regard, in order to assess the influence of Pneumocystis in the lung in the association with SIV infection, Qin et al evaluated cytokine and chemokine gene expression changes in lung tissue in SIV-infected macaques with and without PCP (248).…”
Section: Macrophagesmentioning
confidence: 99%
“…Comprehensive evaluations of the effects of Pneumocystis on gene expression of AMs and lung tissue are beginning to address the complexity of the host-pathogen interaction (37,248). In this regard, in order to assess the influence of Pneumocystis in the lung in the association with SIV infection, Qin et al evaluated cytokine and chemokine gene expression changes in lung tissue in SIV-infected macaques with and without PCP (248). The most upregulated immune genes were found to be those for IFN-␥, IFN-␥-inducible CXCR3, CCR5 ligands, and their cognate chemokine receptors.…”
Section: Macrophagesmentioning
confidence: 99%
“…The potential role of chemokines in Pneumocystis infection has been examined in a number of in vitro and in vivo studies [5-16]. In vitro studies have demonstrated an increase in Cxcr2 ligands [6, 17], while in vivo studies, which were primarily performed in immunosuppressed mice, have shown increased expression of Ccr2, Ccr5, and Cxcr3 ligands [9-11, 14, 15, 18]. However, no study to date has comprehensively examined chemokine and chemokine receptor responses in immunocompetent hosts.…”
Section: Introductionmentioning
confidence: 99%
“…), which was defined by weight loss, loss of CD4 ϩ T lymphocytes, and/or development of opportunistic infections, such as Pneumocystis jirovecii pneumonia. These animals and their clinicovirologic states have been presented previously (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…Adult cynomolgus macaques (Macaca fascicularis) were used in this study and were inoculated intrarectally with the pathogenic SIV/DeltaB670 isolate (11). These animals and their clinicovirologic states have been described previously (12)(13)(14). Fixation and processing of tissues at necropsy were completed as described previously (15).…”
Section: Animals and Tissuesmentioning
confidence: 99%